2021
DOI: 10.1038/s41598-021-84031-0
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in intestinal microbiota diversity, composition, and function in patients with sarcopenia

Abstract: Abstract16S rRNA sequencing of human fecal samples has been tremendously successful in identifying microbiome changes associated with both aging and disease. A number of studies have described microbial alterations corresponding to physical frailty and nursing home residence among aging individuals. A gut-muscle axis through which the microbiome influences skeletal muscle growth/function has been hypothesized. However, the microbiome has yet to be examined in sarcopenia. Here, we collected fecal samples of 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 77 publications
4
99
3
Order By: Relevance
“…Moreover, SCFAs not only serve as an energy source for the host, but also have a significant impact on immunity. Butyrate is a short-chain fatty acid with anti-inflammatory and anticancer properties, and recent studies have reported an association with sarcopenia [34]. Interestingly, based on the recently published results for ameliorates sarcopenia of HY7715 [35], considering the changes in the butyrate concentration and butyrate-producing bacteria in the HY7715-treated group, the HY7715 intake has the potential to improve sarcopenia, but studies on the interaction between the microbiome and its metabolites should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SCFAs not only serve as an energy source for the host, but also have a significant impact on immunity. Butyrate is a short-chain fatty acid with anti-inflammatory and anticancer properties, and recent studies have reported an association with sarcopenia [34]. Interestingly, based on the recently published results for ameliorates sarcopenia of HY7715 [35], considering the changes in the butyrate concentration and butyrate-producing bacteria in the HY7715-treated group, the HY7715 intake has the potential to improve sarcopenia, but studies on the interaction between the microbiome and its metabolites should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…_.: indicates that the OTU cannot be further classified to the next level significantly positively correlated with grip strength in adults age ≥60 years old. 38 After controlling for body fat mass or BMI, our findings suggested only the abundance of genera Faecalitalea and Pyramidobacter are significantly associated with skeletal muscle mass. However, further studies are needed to validate these findings.…”
Section: Discussionmentioning
confidence: 67%
“…Besides, Ruminiclostridium 9 belongs to the Ruminococcaceae family; reportedly, a high abundance of Ruminococcaceae in the cecum could effectively prevent malnutrition ( Million et al, 2016 ). The short-chain fatty acid butyrate-producing bacteria, such as Ruminococcaceae , Odoribacter , Intestinimonas , and Faecalibaculum ( Kang et al, 2021 ; Liu et al, 2021 ). Notably, the abovementioned bacteria were more abundant in HFD-PREP gt than HFD-WT mice.…”
Section: Discussionmentioning
confidence: 99%